KNOWLEDGE TRANSFER IN INTRAORGANIZATIONAL NETWORKS: EFFECTS OF NETWORK POSITION AND ABSORPTIVE CAPACITY ON BUSINESS UNIT INNOVATION AND PERFORMANCE. - Tsai, W. (Academy of Management Journal, 2001)
Inside a multiunit organization, units can learn from each other and benefit from new knowledge developed by other units. Knowledge transfer among organizational units provides opportunities for mutual learning and interunit cooperation that stimulate the creation of new knowledge and, at the same time, contribute to organizational units' ability to innovate (e.g., Kogut & Zander, 1992; Tsai &